1983
DOI: 10.1203/00006450-198305000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Infection in the Infant Mouse

Abstract: SummaryA nonlethal influenza infection [A/PC/1/73 (H3Nz)l was given to infant mice to determine (1) the pathology of tracheal epithelium and lung, (2) the time course of viral shedding from the nose and lung, and (3) the subsequent development of protective immunity during adulthood.Both desquamation of the tracheal epithelium and lung pathology similar to that described in adults after influenza infection were observed in the infant. Animals infected at 3 days of age show virus shedding in 12 of 13 infant mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…It has previously been demonstrated that acquisition of influenza-specific antibody in neonatal mice is predominantly mediated by breast-feeding [23]. We hypothesized that enhanced protection of pups of dams receiving iPR8+Advax could likewise be due to enhanced breast milk transfer of maternal IgG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been demonstrated that acquisition of influenza-specific antibody in neonatal mice is predominantly mediated by breast-feeding [23]. We hypothesized that enhanced protection of pups of dams receiving iPR8+Advax could likewise be due to enhanced breast milk transfer of maternal IgG.…”
Section: Resultsmentioning
confidence: 99%
“…Maternal antibody acquired by pups through transplacental transfer or breast milk provides a critical mechanism of protection against infection during the period of neonatal immune immaturity [22, 23]. We wished, therefore, to see whether the addition of Advax adjuvant to vaccine administered to pregnant mothers could enhance protection of their unimmunized pups.…”
Section: Resultsmentioning
confidence: 99%
“…In a mouse model using 3 day old animals, 1 of 5 animals exhibited positive antibody titers at 13 days postinfection compared to 5 of 5 adults [36]. The vast majority of additional data available in relation to influenza-specific immune responses in infants is derived from studies of vaccination in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Virus shedding persisted on day 7 in 2 of 10, 3 of 11, and 3 of 9 animals infected with the H3N2, HlNl, and CR29 strains, respectively. Likewise, in infant and adult mice infected with another H3N2 strain (A/PC/l/73), peak nasal wash virus titers were 103.5 50% egg infective doses and virus shedding ceased before day 11 (29). Although virus titers from nasal turbunate homogenates were higher in infant rats infected with the H3N2, HIN1, and CR29 strains (3), Reuman et al found that virus titers were significantly lower in nasal homogenates than in nasal washes performed on the same animals (29).…”
Section: Downloaded Frommentioning
confidence: 97%